Effect of Dislocation Arrays at Grain Boundaries on Electronic Transport Properties of Bismuth Antimony Telluride: Unified Strategy for High Thermoelectric Performance. Issue 20 (6th April 2018) - Hwang, Jae‐Yeol; Kim, Jungwon; Kim, Hyun‐Sik; Kim, Sang‐Il; Lee, Kyu Hyoung; Kim, Sung Wng
Abstract: Taming electronic and thermal transport properties is the ultimate goal in the quest to achieve unprecedentedly high performance in thermoelectric (TE) materials. Most state‐of‐the‐art TE materials are inherently narrow bandgap semiconductors, which have an inevitable contribution from minority carriers, concurrently decreasing Seebeck coefficient and increasing thermal conductivity. Nevertheless, the restraint control of minority carrier transport is seldom considered as a key element to enhance the TE figure of merit ( zT ). Herein, it is verified that the localized dislocation arrays at grain boundaries enable the suppression of minority carrier contribution to electronic transport properties, resulting in an increase of the Seebeck coefficient and the carrier mobility in bismuth antimony tellurides. It is also suggested that the suppression of minority carriers via the generation of dislocation arrays at grain boundaries is an effective and noninvasive strategy to optimize overall electronic transport properties without sacrificing predominant characteristics of majority carriers in TE materials. Abstract : The localized dislocation arrays at grain boundaries enable the selective suppression of minority carrier contribution to electronic transport properties without sacrificing characteristics of majority carriers, resulting in an increase of overall Seebeck coefficient and carrier mobility in bismuth antimony tellurides. This finding provides an effective and noninvasive paradigm to optimize electronic transport properties of conventional thermoelectric materials.